(untitled) (Research, Society and Development, 2023)
The objective of this study was to describe the occurrence of perceived occupational violence among nurses and nursing technicians working in Family Health Strategy teams. Methodology: This is an exploratory, cross-sectional cohort study with a quantitative approach, carried out with 251 nursing professionals from the Family Health Strategy in the municipality of Uberlândia-MG, from August to October 2020. Results: The concern for workers’ health nursing is essential so that assistance to users of the Unified Health System is comprehensive and qualified. In view of this, it was evident that acts of violence against nursing professionals were committed by other professionals in the area and by users of the public service, with the prevalence being verbal abuse by patients and sexual harassment by bosses and/or supervisors. Conclusion: Therefore, it is emphasized that such situations of violence are reproduced due to the patients’ lack of knowledge regarding the responsibilities of each Health Care sector in Brazil, and the lack of professional ethics practice by health service managers.